Law instead of Christian morality: Leon Petrazhycki’s paradox of love ethics - Timoshina, Elena (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2024)
The article deals with the ideas of the Russian-Polish jurist, philosopher of law L. Petrazhycki (1867–1931) about the social significance of morality and law as the means to achieve a “supralegal” and “supramoral” ideal of love. His reasoning demonstrates a deep theoretical analysis of law in its correlation with Christian morality. Petrazhycki draws a distinction between law and morality based on the nature of duties: in law duties are dependent on external authority or another’s claim, while in morality they are not. The author analyses this distinction and argues that is consistent with the Christian view on human freedom. Based on the analysis of Petrazhycki’s concept of intuitive law, it is concluded that law and morality share the same psychological mechanism of self-obligation, which makes is possible to postulate the inner morality of law. The idea of an inner morality of law is further developed by Petrazhycki in his concept of intuitive law which is seen as the imperative of conscience, as initial intuition of justice. The concept of intuitive law embodies an integrated moral and legal experience of a person and is used to describe a situation in which the right ethical choice is made — such a choice corresponds to both moral imperatives and the requirements of justice. The paradox of Petrazhycki’s ethics of love consists in the fact that as the most effective tool for its achievement, the scientist chooses positive law, which has mechanisms of motivational pressure and physical coercion that are absent in morality and intuitive law, while the preaching of the Gospel message, associated with the freedom of its acceptance, turns out to be unsuitable for achieving the ideal of universal love. However, the transformation of freely executed imperatives of Christian morality into legal duties causes an effect opposite to the goal pursued, as it deprives a person from both morality and freedom as its necessary condition. The author draws a parallel between the ideal constructed by Petrazhycki and the “reign of peace and happiness” without freedom that was described by Dostoevsky in “The Grand Inquisitor”.